Multi-hierarchy virtual-water management– A case study of Hubei Province, China. (15th April 2021) - Fu, Yupeng; Huang, Guohe; Liu, Lirong; Li, Jianyong; Zhang, Xiaoyue; Zhai, Mengyu; Pan, Xiaojie
Abstract: Facing the prospective conflict between fast economic growth and water-use challenges, it is desired to explore the relationship between industrial structure and virtual-water flow in a socio-economic system to support the formulation of water-resource management related legislation. In this study, a multi-hierarchy industrial virtual water network model (MIVWN) was developed for analyzing the status of varied industrial sectors in the virtual-water system. A special case study for Hubei Province, China, was conducted to demonstrate the potential profits of its use in the formulation of water-resource management related legislation. Specifically, multi-hierarchy scenarios for system identification were performed to get more insights on the complex interrelationships among various industrial sectors. It is found that the industrial sectors have low water-use efficiency; and the mutual connections of virtual water between various industrial sectors are limited in Hubei. For the substantial industrial sectors, it is of vital importance to upgrade the upstream and downstream supply chains. For the isolated sectors, the decision maker should commit to enhance their virtual water exchanges with other sectors. It is expected that the results will provide a solid basis for supporting the application of an effective water-resource management strategies for industrial sectors. Highlights: A multi-hierarchy virtual-water network of industry model is developed. Industrial sectors are clustered to evaluate virtual-water utilization efficiency. Aggregated, Disaggregated, and Dimensional Hierarchy scenarios are designed. Industrial sectors have low water-use efficiency. Mutual connections of virtual water between industrial sectors are not enough.